Radar Scattering Analysis of Multi-Scale Complex Targets by Fast VSBR-MoM Method in Urban Scenes - Zhou Cong; Jihong Gu; Ying Zhang; Jie Yang; Dazhi Ding (Remote Sensing)
An innovative and efficient hybrid technique, which combines the Method of Moments (MoM) with Volume Meshed Shooting and Bouncing Ray (VSBR), is presented to analyze the scattering of metallic–dielectric mixed multi-scale structures in urban scenes. Additionally, the technique can rapidly generate radar images at different angles, which is useful for the video remote sensing community. By dividing the mixed multi-scale targets into sub-regions, different solvers are employed to compute the scattering contributions based on their varying electrical sizes. For large-scale sub-regions, the VSBR method is employed on both the medium and metal parts, leading to a multilevel electromagnetic field including both the direct induced field and the multi-reflection field. This field contributes to the integral equation in the MoM sub-regions. Additionally, interactions from the MoM region are considered within the VSBR region, followed by a surface current integration to compute the scattered field. When addressing mixed multi-scale electromagnetic problems, this technique proves to be more efficient and easier to implement in general-purpose computer codes. Furthermore, this method is accelerated using the local coupling (LC) theory and fast multipole method (FMM). Using this fast computational method, efficient simulation results of radar images at different angles for the scenes can be obtained and the numerical results demonstrate the efficiency and accuracy of the proposed method.